Gambaran Asam Urat pada Lansia di Posyandu Melati Kecamatan Cipayung Jakarta Timur - Afif Amir Amrullah; Kareena Sari Fatimah; Nikita Puteri Nandy; Wulan Septiana; Siti Nurul Azizah; Nursalsabila Nursalsabila; Adzkia Hayyanal Alya; Dayini Batrisyia; Nabiilah Salsa Zain (Jurnal Ventilator, 2023)
Gout is a type of arthritis that occurs due to the expansion of uric acid crystals that occur in several joints. The average level of uric acid in the blood depends on gender and age. Someone who is old is usually more susceptible to advanced uric acid. This is the background of this research. This study aims to describe uric acid levels in the elderly at Posyandu Melati, Cipayung District, East Jakarta. This type of research is descriptive with a cross sectional design. The sample selection was obtained by purposive sampling technique with a large sample of 30 people. The results showed that the average uric acid level of male respondents was higher, namely 6.8 mg/dl compared to the average uric acid level of female respondents, which was 5.3 mg/dl. From the results of this study, it can be concluded that uric acid levels in elderly men are higher than those in elderly women, although the levels are still relatively normal.